Computational Studies for Structure-Based Drug Designing Against Transmembrane Receptors: pLGICs and Class A GPCRs - Payghan, Pavan V.; Bera, Indrani; Bhattacharyya, Dhananjay; Ghoshal, Nanda (Frontiers in Physics, 2018)
Biological cell is the fundamental building block of every living system. The plasma membrane, a phospholipid bilayer consisting of two asymmetric leaflets, defines its existence by separating the interior from the exterior. This low dielectric barrier selectively prevents the passage of hydrophilic and charged compounds including small ions. Integral transmembrane proteins span the entire bilayer and take part in small-molecule transport and complex signaling pathways while functioning as receptors and/or ion channels. These proteins carry important biological functions and hence are attractive drug targets. Present review considers the members of two important protein superfamilies that provided the major pharmaceutical drug-targets, viz., Cys-loop pentameric ligand gated ion channels (pLGICs) and class A G-protein-coupled receptors (GPCRs). The crystal structures of integral membrane proteins (IMPs) are difficult to obtain. Their unavailability has limited the structural investigation and associated structure-based drug designing (SBDD). However, recent advancement in crystallographic techniques yielded some important crystal structures. The advancement of computational science guided IMPs study even in the absence of crystal structures through the homology/comparative modeling approaches. These proteins possess multiple ligand binding sites including both orthosteric and allosteric sites. Addressing the multidimensional problem of understanding the structure and dynamics of such big proteins, multisite-protein-ligand complexes is now possible with molecular dynamics simulation approach, enabled with highly enhanced computational power. Overall the discussion highlights the understanding of structure-function relationship that guides SBDD of these interesting and important transmembrane proteins.